EFFECT OF AGE AND EDUCATION LEVEL ON OPERATOR’S PERFOMANCE WITH HARVESTER VIRTUAL REALITY SIMULATOR - Lopes, Eduardo Silva; Pagnussat, Millana Bürger (Floresta, 2018)
The aim of this study was to analyze the effect of age and education level in the training using harvester virtual reality simulator (HVRS). The study was developed in the Operator Training Forest Center (CENFOR), using data of 124 professionals trained in HVRS. This specialized software were used to simulate machine operation, so that also were used how data source to measure performance of the operating variables in the beginning and end of two operating modules. The results indicate that younger people performed better in the studied operating variables because they could better assimilate the transmitted techniques and developed faster, showing that age is an important element in identifying the ideal profile of people to be recruited as future Harvester operators.